Italian youth in international context belonging, constraints and opportunities - Cuzzocrea, Valentina; Bello, Barbara Giovanna; Kazepov, Yuri (Youth, young adulthood and society, 2020)
"Italy is not a country for young people. Why? This book provides a unique and in-depth collection of empirical and theoretical material providing multiple answers to this question whilst investigating the living conditions of young people in Italy today. By bringing together a variety of approaches and methods, the authors of this collection analyze Italian youth through the lenses of three dimensions: 'Activism, participation and citizenship', 'Work, Employment and Careers' and 'Moves, Transitions and Representations'. These dimensions are the analytical building blocks for challenging stereotypes and unveiling misinterpretations and taken-for-granted assumptions that portray young people in Italy as selfish, 'choosy', and unwilling to make sacrifices, commit and manage an independent life. These prejudices often underplay the role of constraints they are facing in the transition to adulthood. Studying Italian youth, therefore, not only allows us to capture their peculiar characteristics, but also to reflect more broadly on the conceptual toolbox we need in order to understand contemporary youth more generally. By doing so, the volume aims to contribute to international discussion on the youth condition in Europe"--